The dictionary of synonyms as a resource for expanding WordNet - Gómez Guinovart, Xavier (2014)
In this paper, we present the foundations for a lexical acquisition experiment designed in the framework of the SKATeR research project and aimed to the expansion of the Galician WordNet using the lexicographical data collected in a "traditional'' Galician dictionary of synonyms.